Corporate Financial Performance Analysis Multifinance Post-Economic Crisis Year 2004 2008 - Ekowati, Dhiana (Accounting, 2010)
This study aims to analyze the financial statements of financial performance, particularly finance companies / multi listed listed on the Indonesia Stock Exchange (IDX) and registered at the Indonesian Financial Services Association (IFSA). Time study conducted in March until June 2009. The first analysis tool which uses financial ratios of a general nature that is using liquidity ratios, solvency ratios, profitability ratios, activity ratios, while the second analysis tool that uses Z-Score Formula. In the analysis of this data is not all financial ratios we calculate. Results of analysis seen from the level of liquidity it can be said that the current financing perusahaa ratio is good, it would be better if the finance company reviewing the performance of previous keuagan whether the company has particularly assets sufficient to ensure future debt before taking keputusahan for debt or issue new shares; In view of both its solvency level dept and dept to equity ratio, the ratio is good, because of the large percentage of the total debt below 50% means that the average company’s total assets be financed by debt below 50% so it is likely to settle the obligation can be paid on time ; In view of the activity level can be said about either means total assets turnover is very slow to increase sales and generate profits; In view of the level of profitability is very good where the average finance company had net income above 20% even have company financing that could increase the net profit margin ratio of 100% of PT Buana Finance in 2007. The second analysis results show the company’s financial soundness is almost the average value is above the standard value of Z-Score is > 2.60, this shows that the company has good financial performance so the impact on public confidence to invest in companies. Keyword: Finance, Multifinance, Economic Crisis